Upaya Peningkatan Penguasaan Kosa Kata Bahasa Inggris Melalui Program Tiket Bahasa SMP Islam Jabal Hikmah - Mashar, Mashar (Lembaga Bale Literasi, 2023)
Studying English well, correctly and appropriately is something that must be done, because the use of English is currently very much needed for various communication needs both at home and abroad. One of the basic things in learning English is mastering English vocabulary. An approach that can be applied to increase understanding of vocabulary is to use the Tiket Bahasa approach. The aim of this research is to determine the effect of using the